Center on the Economics and Management of Education and Training Systems (CEMETS). Intermediary Research Report - Katherine Caves; Ursula Renold (ETH Zurich, KOF Swiss Economic Institute, 2016)
The purpose of CEMETS' initial research project is to understand why the implementation of labor market-oriented education systems reforms succeed and fail. Findings should be generalizable to theory and to concrete situations so that we can inform both research and practice. We build and compare case studies of reform projects through the CEMETS Economic Policy Development Research Program for Education Reform Leaders. The centerpiece of that program is a ten-day summer institute during which reform teams learn about VET theory, policy, and practice and revise their reform plan. Each of the reform projects is a case study and we follow them over time as they implement their reforms.
Keywords: 330; Berufsbildung; Berufsbildungspolitik; Arbeitsmarktforschung; Welt